2016
DOI: 10.1016/j.exger.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Absence of morphological and molecular correlates of sarcopenia in the macaque tongue muscle styloglossus

Abstract: Introduction Equivocal decline of tongue muscle performance with age is compatible with resistance of the tongue to sarcopenia, the loss of muscle volume and function that typically occurs with aging. To test this possibility we characterized anatomical and molecular indices of sarcopenia in the macaque tongue muscle styloglossus (SG). Methods We quantified myosin heavy chain (MHC), muscle fiber MHC phenotype and size and total and phosphorylated growth- and atrophy-related proteins by sodium dodecyl sulfate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 83 publications
(103 reference statements)
1
8
0
Order By: Relevance
“…Different age ranges, muscle sample locations, and muscle fiber selection parameters may have contributed to the divergent findings. Mixed results have also been reported on the impact of aging on the extrinsic lingual muscles . Because imaging and electromyographic studies have indicated that the transverse and verticalis muscles may work with the genioglossus to propel the bolus during swallowing, decreasing muscle fiber size in the transverse and verticalis muscles, as reported in our study, may contribute to the reductions in maximum tongue pressure found with age …”
Section: Discussionsupporting
confidence: 40%
“…Different age ranges, muscle sample locations, and muscle fiber selection parameters may have contributed to the divergent findings. Mixed results have also been reported on the impact of aging on the extrinsic lingual muscles . Because imaging and electromyographic studies have indicated that the transverse and verticalis muscles may work with the genioglossus to propel the bolus during swallowing, decreasing muscle fiber size in the transverse and verticalis muscles, as reported in our study, may contribute to the reductions in maximum tongue pressure found with age …”
Section: Discussionsupporting
confidence: 40%
“…Furthermore, many suprahyoid, infrahyoid, pharyngeal and laryngeal muscles receive constant input stimulation from the respiratory center, and their activities are potentially synchronized with the contraction and relaxation of the diaphragm. In particular, the styloglossus muscle has been shown to exhibit resistance against sarcopenia both immunohistochemically and molecularly . Such activities are believed to render these muscles more resistant to disuse‐related atrophy than general somatic muscles.…”
Section: Specificity Of the Swallowing Musclesmentioning
confidence: 99%
“…In particular, the styloglossus muscle has been shown to exhibit resistance against sarcopenia both immunohistochemically and molecularly. 26 Such activities are believed to render these muscles more resistant to disuse-related atrophy than general somatic muscles. Thus, these differences should be taken into consideration when the pathophysiology of sarcopenia is discussed.…”
Section: Specificity Of the Swallowing Musclesmentioning
confidence: 99%
“…Features common to sarcopenic appendicular muscle, i.e., a shift to slower myosin heavy chain isoforms, type II muscle fiber atrophy and neuromuscular junction dysmorphology, are absent or minimal in rat tongue muscles (30,31). In particular, the styloglossus muscle has been shown to exhibit resistance against sarcopenia both molecularly and immunohistochemically (32). It was reported that normal and effortful swallow pressures do not decline with age (13) and by some measures tongue functional reserve is maintained with age (33).…”
Section: Discussionmentioning
confidence: 99%